1990
DOI: 10.1128/aac.34.9.1749
|View full text |Cite
|
Sign up to set email alerts
|

Alpha interferon (2b) in combination with zidovudine for the treatment of presymptomatic feline leukemia virus-induced immunodeficiency syndrome

Abstract: The therapeutic efficacies of human recombinant alpha interferon (IFN-alpha), IFN-alpha plus zidovudine (AZT), and AZT alone were evaluated in presymptomatic cats with established feline leukemia virus (FeLV)-acquired immunodeficiency syndrome (FAIDS) infection and high levels of persistent antigenemia. Subcutaneous injection of 1.6 x 10(6) U of human recombinant IFN-alpha 2b per kg delivered peak concentrations in plasma of 3,600 U/ml at 2 h postadministration with a half-life of elimination of 2.9 h. This do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
40
2
7

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 45 publications
4
40
2
7
Order By: Relevance
“…Regarding the use of IFNs in FeLV-and FIV-associated diseases, some studies showed encouraging and sometimes dramatic therapeutic effects on symptomatic as well as asymptomatic cats, [11][12][13][14][15] whereas other more recent studies failed to confirm previous observations. 16,17 The discrepancies may be attributed, at least in part, to different study designs, notably regarding (sub)types of IFN, species of origin, purity of preparations, treatment route, dosage, and schedule, as well as the age and pathological stage of FeLVinfected cats.…”
contrasting
confidence: 38%
“…Regarding the use of IFNs in FeLV-and FIV-associated diseases, some studies showed encouraging and sometimes dramatic therapeutic effects on symptomatic as well as asymptomatic cats, [11][12][13][14][15] whereas other more recent studies failed to confirm previous observations. 16,17 The discrepancies may be attributed, at least in part, to different study designs, notably regarding (sub)types of IFN, species of origin, purity of preparations, treatment route, dosage, and schedule, as well as the age and pathological stage of FeLVinfected cats.…”
contrasting
confidence: 38%
“…116 One study evaluated the therapeutic efficacy of high dose IFN-α (1.6 x 10 4 to 1.6 x 10 6 IU/kg SC q24h) in experimentally FeLV-infected cats with persistently high levels of antigenaemia. 46 Treatment resulted in a significant decrease in circulating FeLV antigen beginning 2 weeks after the initiation of therapy (EBM grade II). 46 However, because of anti-IFN-α antibody development, cats became refractory to therapy 3 or 7 weeks after starting treatment.…”
Section: -113mentioning
confidence: 99%
“…46 Treatment resulted in a significant decrease in circulating FeLV antigen beginning 2 weeks after the initiation of therapy (EBM grade II). 46 However, because of anti-IFN-α antibody development, cats became refractory to therapy 3 or 7 weeks after starting treatment. 46 In a placebo-controlled, doubleblind study in naturally FeLV-infected cats using a similar high dose regimen, treatment with IFN-α (1 x 10 5 IU/kg SC q24h for 6 weeks) did not lead to a significant improvement in clinical, laboratory, immuno logical or virological parameters (EBM grade I).…”
Section: -113mentioning
confidence: 99%
See 2 more Smart Citations